PENGARUH PENDANAAN MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN - Afifah, Marisa Mursyidhatul; Aisjah, Siti (Jurnal Management Risiko dan Keuangan, 2022)
The objective of this research is to assess and analyze the effects of working capital financing on firm profitability. This study was conducted on food-and-beverages sub-sector companies listed on the Indonesia Stock Exchange in the 2016-2020 period. Using purposive sampling method and non-random sampling, twelve companies were selected as the sample, resulting in sixteen observations. Working Capital Financing (WCF) was used to measure the independent variable so that the approach type of the financing can be determined, while Return on Assets (ROA) was used to measure the dependent variable. Descriptive statistics and simple linear regression were used to analyze the data, while F test and Coefficient of Determination (R2) were applied in IBM SPSS 26 to test the hypotheses. This study finds that working capital funding with a conservative approach has a negative and significant effect on profitability. Furthermore, companies that increase their financing on long-term financing source experienced a decline in their profitability.